THE USE OF STATISTICAL ANALYSIS IN THE LITHOSTRATIGRAPHY OF SUBMARINE FAN DEPOSITS. AN EXAMPLE FROM SOUTHEAST GREECE (KARPATHOS ISLAND) - Pantopoulos, G.; Konstantopoulos, P.; Maravelis, A.; Zelilidis, A. (Bulletin of the Geological Society of Greece, 2006)
Examples of various types of statistical analysis of submarine fan bed thickness distributions that have been proposed in the past are reported, as well as an example of their application in Late Eocene-Oligocene submarine fan deposits of SE Greece (Karpathos Island). Generally, the sandstone bed thickness data measured in two outcrops of Karpathos submarine fans seems to follow power law (fractal) cumulative distributions. A deviation from the power law was observed as amalgamationprocedures become more frequent. These observations gave important information about Tertiary turbidite sedimentation in the area which probably was punctuated and had a single main sediment source. Information taken from statistical analysis of submarine fans bed thickness data has immediate applicability in hydrocarbon exploration because sandstones constitute ideal reservoirs.